The Levels of Oxidized Phospholipids in High-Density Lipoprotein During the Course of Sepsis and Their Prognostic Value - Li, Zhaohong; Luo, Zengtao; Shi, Xiaoqian; Pang, Baosen; Ma, Yingmin; Jin, Jiawei (Frontiers in Immunology, 2022)
Purpose To examine the levels of 1-palmitoyl-2-(5-oxovaleroyl)-sn-glycero phosphatidylcholine (POVPC) and 1-palmitoyl-2-glutaroyl-sn-glycero-phosphatidylcholine (PGPC) (the oxidized phosphatidylcholines) in HDL during the course of sepsis and to evaluate their prognostic value. Materials and Methods This prospective cohort pilot study enrolled 25 septic patients and 10 healthy subjects from 2020 to 2021. The HDLs were extracted from patient plasmas at day 1, 3 and 7 after sepsis onset and from healthy plasmas (total 81 plasma samples). These HDLs were then subjected to examining POVPC and PGPC by using an ultra-high performance liquid chromatography coupled with tandem mass spectrometry (UHPLC-MS/MS) system. We further measured the levels of 38 plasma cytokines by Luminex and evaluated the correlation of HDL-POVPC level with these cytokines. Patients were further stratified into survivors and non-survivors to analyze the association of HDL-POVPC level with 28-day mortality. Results Septic patients exhibited significant increase of HDL-POVPC at day 1, 3 and 7 after sepsis onset (POVPC-D1, p=0.0004; POVPC-D3, p=0.033; POVPC-D7, p=0.004, versus controls). HDL-PGPC was detected only in some septic patients (10 of 25) but not in healthy controls. Septic patients showed a significant change of the plasma cytokines profile. The correlation assay showed that IL-15 and IL-18 levels were positively correlated with HDL-POVPC level, while the macrophage-derived chemokine (MDC) level was negatively correlated with HDL-POVPC level. Furthermore, HDL-POVPC level in non-survivors was significantly increased versus survivors at day 1 and 3 (POVPC-D1, p=0.002; POVPC-D3, p=0.003). Area under ROC curves of POVPC-D1 and POVPC-D3 in predicting 28-day mortality were 0.828 and 0.851. POVPC-D1and POVPC-D3 were the independent risk factors for the death of septic patients (p=0.046 and 0.035). Conclusions HDL-POVPC was persistently increased in the course of sepsis. POVPC-D1 and POVPC-D3 were significantly correlated with 28-mortality and might be valuable to predict poor prognosis.